2004
DOI: 10.1111/j.1475-1313.2004.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a prototype Minified Augmented‐View device for patients with impaired night vision*

Abstract: An evaluation was carried out of the first prototype (LV-3) of a new night vision device, which incorporates visual field expansion through minification (Minified Augmented-View), to provide feedback for continuing development. Six subjects with night blindness completed visual function measurements and indoor mobility assessments without a device, with the LV-3 and with a commercially available comparison device (the Multi-Vision) at light levels representative of well lit and poorly lit streets. Device perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…18 The use of minification seems to be logical, but partial rejection and failure of these devices has been reported. 15,16,19,20 For instance, Lowe and Drasdo 19 found that a reversed telescope with 3 ϫ minification did not help subjects with peripheral field loss to perform a simple visual search task. Kennedy et al 15 reported that subjects found it difficult to walk while looking through reversed telescopes and that good visual acuity (VA) was needed to succeed with the use of field expanders.…”
mentioning
confidence: 99%
“…18 The use of minification seems to be logical, but partial rejection and failure of these devices has been reported. 15,16,19,20 For instance, Lowe and Drasdo 19 found that a reversed telescope with 3 ϫ minification did not help subjects with peripheral field loss to perform a simple visual search task. Kennedy et al 15 reported that subjects found it difficult to walk while looking through reversed telescopes and that good visual acuity (VA) was needed to succeed with the use of field expanders.…”
mentioning
confidence: 99%
“…This might have been caused by the lack of appropriate training for adaptation to using a 49 minified image and/or transmittance of the see-through display; notably, the walking time with the device improved with each repetition (average walking time: practice one, 32.88 ± 13.76 s; practice two, 27.38 ± 10.31 s; walking test, 24.86 ± 8.66 s). As discussed in previous reports [8,9,11,12], the improvement of mobility in darkened conditions is explained by the effect of visual field expansion through minification of the view as well as by the ability to see the objects. In this study, we used only a micro lens (f3.8 F2.0) to create the necessary conditions, the magnification percentage of the image, however, can be adjusted easily by changing the camera lens.…”
Section: Discussionmentioning
confidence: 54%
“…Since the 1970s, several types of devices have been evaluated to address mobility problems due to night blindness [7][8][9][10][11][12][13][14]. Berson et al [7] first reported the helpfulness of a night vision enhancement device based on a military light-intensifier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of such devices is to augment or enhance the visual information available to the patient to help avoid mobility mishaps like falls and collisions. These visual aids range from optical devices, based on prisms fixed to eye glasses which direct the image from near-peripheral to the residual functioning central areas of the visual field [Peli 2000;Woods and Peli 2002], to head-worn electronic displays [Luo, et al 2005;Vargas-Martin and Peli 2002], which apply real-time image processing such as edge detection and use image minification to expand the visual field [Bowers, et al 2004;Luo and Peli 2006a;Vargas-Martin and Peli 2002]. However, although patients happily volunteer subjective reports on their usefulness, it is difficult to obtain an objective and quantitative assessment that can predict the benefits or problems a device would introduce in normal everyday use.…”
Section: Motivationmentioning
confidence: 99%